Pengaruh Religiusitas Terhadap Kesejahteraan Subjektif Pada Umat Beragama - Ambarukmi, Kemuning; Savira, Siti Ina (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Indonesia is among the top 20 most religious countries, with religiosity levels between 80% and 90%. Despite this, religious-motivated terror threats remain common, negatively affecting both victims and society. Terrorists often use religious justifications for their actions, whereas others find that their faith and charitable acts enhance their happiness and well-being. This study aims to investigate the influence of religiosity on subjective well-being. Using a quantitative method, the study involved 208 residents of Tropodo Village aged over 17. It employed two instruments: The Modified BBC Subjective Well-Being Scale (BBC-SWB) and The Centrality of Religiosity Scale (CRS). Simple regression analysis showed a significant influence of religiosity on subjective well-being (p-value < 0.001). The R Square value of 0.161 indicates that religiosity accounts for 16.1% of the variance in subjective well-being.